TWO-CASCADE REGENERATIVE AMPLIFIERS OF O-TYPE OF THE SUBMILLIMETRIC WAVE BANDS - A. V. Aksenchyk; I. F. Kirinovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The mathematical model of the two-cascade orboklystron-amplifier with sheet beams is formulated. Calculations of amplitude characteristics of regenerative amplifiers on frequency of 180 GHz are resulted. Calculation electronic efficiency of two-cascade orboklystron-amplifiers with sheet beams on frequency of 180 GHz can reach values of 5 %, electronic power 16 W, gain 35 dB.